Very Long Chain Marine n-3 Polyunsaturated Fatty Acids in Atherothrombotic Heart Disease. A Brief Review, with a Focus on Metabolic Effects - Arnesen, Harald (Nutrients, 2020)
The global burden of atherothrombotic heart disease should be considered as a life-style disorder where differences in dietary habits and related risk factors like limited physical activity and adiposity together play important roles. Related metabolic changes have been scientifically elucidated in recent decades, and the role of the very-long-chain marine fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) have been much focused on, especially their possible effects on processes like inflammation and thrombosis. In the present brief review of related metabolic mechanisms, the effects of these fatty acids in a clinical setting have been referred to, including some of the authors’ work on this topic. The main focus is the divergent results in the field and the important differences between the study population, the type of supplements and fresh marine sources, the proportion of EPA versus DHA dosages, and the duration of supplementation in clinical trials. We conclude that daily intake of at least 1 g of EPA + DHA may improve a dysmetabolic state in the population. The potential to reduce the risk and progression of atherothrombotic heart disease is still a matter of debate.